Regulatory Disharmony Paradigms and Patterns in Islamic Finance: Integrative Strategy for Islamic Law-Based Transformation - Affandi, Ahmad Zulkifli; Kurniati, Kurniati; Ilyas, Musyfikah (Green Publisher Indonesia, 2025)
This study aims to analyze the patterns of regulatory disharmony in Indonesia’s Sharia digital economy and propose an integrative harmonization strategy based on Islamic law principles to strengthen institutional synergy, legal certainty, and sector competitiveness. This normative-juridical research employs a qualitative descriptive-analytical approach, using secondary data from laws, regulations, fatwas, official reports, and academic literature. Data were analyzed through content and thematic analysis to identify regulatory gaps and formulate policy recommendations. The study identifies four main patterns of disharmony: (1) delayed DSN-MUI fatwas on fintech innovations, (2) dual OJK-BI authority in bank-fintech supervision, (3) unclear regulations on blockchain and smart contracts, and (4) vulnerability to Sharia-based fraud. These issues stem from weak coordination among OJK, BI, DSN-MUI, the Ministry of Cooperatives, and the Ministry of MSMEs. Regulatory harmonization is essential to unlock the full potential of Indonesia’s Sharia digital economy. An integrative strategy involving a Regulatory Harmonization Task Force, an integrated information system (SITRFES), joint SOPs, and a phased implementation roadmap (2026–2031) is proposed to enhance coordination, accelerate innovation, and ensure Sharia compliance. The findings offer actionable insights for policymakers and regulators to strengthen cross-institutional synergy, improve legal certainty, and position Indonesia as a resilient and competitive global hub for Islamic finance. Lessons from Malaysia’s BNM-SAC model and the UAE’s DFSA-HSA framework provide valuable benchmarks for implementation.